Effects of particle size and moisture levels in mixed rations on the feeding behavior of dairy heifers. (11th June 2014) - Khan, M. A.; Bach, A.; Castells, Ll.; Weary, D. M.; von Keyserlingk, M. A. G.
<x content-type="archive" xml:space="preserve">Abstract</x> Two experiments on replacement heifers (175±12 days of age) assessed the effects of forage particle length and moisture on feeding behavior. Both experiments used a replicated 3×3 Latin square design, with nine heifers per replication and three periods of 9 days each. Each group of nine heifers was housed in one pen with access to three electronic feed bins. In Experiment 1, hay chopped at different lengths was incorporated into three total mixed rations (TMR) all having the same ingredient and nutrient composition but differing in the percentage of long particles (>19 mm): 60% (Short), 64% (Medium) and 72% (Long). In Experiment 2, heifers were fed a TMR with the same ingredient and nutrient composition but differing in moisture content: 65% DM (Dry), 50% DM (Moderate), and 35% DM (Wet). In both experiments, feeding behavior during the last 5 days of each period was analyzed using a mixed model accounting for the fixed effects of treatment and period, and the random effects of replication and animal. In Experiment 1, dry matter intake (DMI) and eating rate (DMI/min) tended to increase, whereas daily eating time decreased as the feed particle size decreased. Heifers fed the Long diet selected in favor of long particles (>19 mm) and against Short (1.18 to 8 mm) and fine (<1.18 mm) particles; heifers fed the Short diet selected against long particles and in favor of short and fine particles. Heifers fed the Medium diet showed a preference for medium particles with no preference for the other particle sizes. In Experiment 2, heifers fed the Dry diet tended to consume more feed than those fed the Moderate and Wet diets, with no differences in feeding behavior or sorting activity. In conclusion the Medium diet minimized sorting without reducing eating rates and intake, and adding water to TMR to achieve a dry matter less than 65% tended to decrease DMI without reducing sorting.